2018
DOI: 10.1002/agr.21585
|View full text |Cite
|
Sign up to set email alerts
|

Chinese consumer preferences for fresh produce: Interaction between food safety labels and brands

Abstract: In this study, 938 consumers in China's Shandong Province were surveyed for their preferences for tomatoes in a real choice experiment varying in three product attributes: food safety label, brand, and price. Using a mixed logit model, results revealed that consumer willingness to pay for organic tomatoes was higher than that for tomatoes labeled as Green or Generally Regarded as Safe (GRS). With regard to brands, consumers prefer brands affiliated with proprietary enterprises over brands held by agricultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 49 publications
4
59
1
1
Order By: Relevance
“…The publications are devoted to the attitude of the population to organic food and to their conditions and stages of production. The review of publications confirms the relevance of the study (Iweala, Spiller, & Meyerding, 2019;Petousi, Daskalakis, Fountoulakis, Stentiford, & Manios, 2019;Zahedipour, Asghari, Abdollahi, Alizadeh, & Danesh, 2019;Yin, Hu, Chen, Wang, & Chen, 2019). http://dx.doi.org/10.15405/epsbs.2019.12.04.192 Corresponding Author: Valentina Ivashova Selection and peer-review under…”
Section: Problem Statementsupporting
confidence: 60%
“…The publications are devoted to the attitude of the population to organic food and to their conditions and stages of production. The review of publications confirms the relevance of the study (Iweala, Spiller, & Meyerding, 2019;Petousi, Daskalakis, Fountoulakis, Stentiford, & Manios, 2019;Zahedipour, Asghari, Abdollahi, Alizadeh, & Danesh, 2019;Yin, Hu, Chen, Wang, & Chen, 2019). http://dx.doi.org/10.15405/epsbs.2019.12.04.192 Corresponding Author: Valentina Ivashova Selection and peer-review under…”
Section: Problem Statementsupporting
confidence: 60%
“…Studies found that consumers tended to purchase FVs from their most trusted FV providers [38] and FV products with official food safety certifications, brands, or labels [29,32,34]. Specifically, a study reported that consumers preferred proprietary enterprise brands over cooperative brands [39].…”
Section: Attitude Towards Fvsmentioning
confidence: 99%
“…In addition to price and quality, certification was found to be associated with the consumption of organic FVs [32,33,39]. More specifically, consumers preferred and trusted certification by nongovernmental organizations (NGOs) and the European Union (EU) over stringent green and government certification labels (e.g., ChinaOrg) [33,39], so they were willing to pay higher prices for certified organic FVs [33].…”
Section: Attitude Towards Fvsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, consumers prefer brands owned by private enterprises, and agricultural cooperatives. This is due to the limited shelf life, small production volumes and quality of natural products [21].…”
Section: Literature Reviewmentioning
confidence: 99%